Does sand content in spawning substrate result in early larval emergence? Evidence from a lithophilic cyprinid fish - Tea Basic; J. Robert Britton; Stephen Rice; Andrew Pledger (2018)
The spawning success of lithophilic salmonids is strongly influenced by the fine sediment content (“fines”) of spawning substrates, yet knowledge on the impacts of fines on the spawning of non‐salmonid lithophiles remains limited, despite their ecological and socio‐economic importance in European rivers. Consequently, the aim here was to use an ex‐situ experiment to investigate the impact of sand content on egg survival and timing of larval emergence of the surface‐spawning cyprinid European barbel Barbus barbus. Thirty incubator boxes within a recirculating system were filled with one of five experimental sediment mixtures (0%–40% sand by mass) that each contained 300 fertilised eggs at a depth of 50 mm. Emerged, free‐swimming larvae were captured and counted daily to assess grain‐size effects on larval survival and emergence. Specifically, total proportion of emerged larvae, cumulative daily proportion of emerged larvae and time required to reach 50% emergence were measured during the study. Whilst the proportion of sand in the sediments did not have a significant impact on egg‐to‐emergence survival (mean survival per treatment 75%–79%), it significantly affected the timing of larval emergence to the water column; early emergence was detected in treatments with elevated sand content (on average, 50% emergence after 12–13 days versus 19 days in the control). Similar to findings from salmonid studies, these results suggest high sand content in spawning gravels can influence timing of larval emergence and potentially cyprinid lithophilic fish survival.